Dante Alighieri's "Comedy": codices, copyists and scriptures - Sandro Bertelli (Annali Online dell'Università di Ferrara. Sezione Lettere)
The paper aims at investigating the manuscript tradition of Dante’s Comedy until the early printed editions. After a brief overview of different typologies of the most ancient manuscript tradition (14th century, first half), the analysis will focus on some famous copyists of the Comedy (e.g. Francesco di ser Nardo da Barberino, the ‘copyist of Parm’), then, it will investigate the main codicological features that identify some of the most important codices of Dante’s masterpiece.